Fight of the Lithuanian Partisans against Collaboration in 1949–1953 - Pocius, Mindaugas (Genocidas ir rezistencija, 2009)
The last period of resistance (1949–1953) is characterized by the extenuation of the underground forces and weakening of the struggle against collaboration. Even though the number of treasons and a scale of collaboration increased, support of the public to the partisans decreased significantly. Sentiments of the adaptation to the existing situation encompassed the broad layers of society, therefore the methods and measures of the partisan fights became mitigated. Verbal and written warnings prevailed. Death penalties most often were imposed on the most ardent helpers of authorities. Collectivization and Sovietization was nearing completion at the end of 1951; repressions against the collaborators with authorities lost importance and meaning.In 1949, LLKS (Lithuanian Fight for Freedom Movement), as the supreme political and military government of Lithuania, made acts, which regulated public relations, uniform, and finally legally enforced the procedure of execution of penalties on the persons accused of collaboration. In judging the persons, suspected of collaboration and criminal crimes, all districts had to be strictly guided by the LLKS Penal Statute.Data identified during investigation and provided in tables reveal that in the last years of resistance, the fight in the essence was directed against party and Soviet activists as well as civil people accused of collaboration. Attacks against MGB officials, MGB Army military men, MVD employees and “stribai” became a matter of minor importance.Analysis of new historical sources does not confirm the version which is imprinted in the historic consciousness of the public about the degeneration of the resistance in the last years because of the more frequent senseless massacre of civil people and their families. On the contrary, it is possible to speak about the considerably softer tactic of the fight against collaborators, as compared to the years 1946–1948. The terrorist actions (family massacre) and excesses against civil and Soviet activists reduced in number. At the last stage of the fight, the underground almost did not exercise broad-scale punitive actions not only because the ranks of partisans became less, but also owing to the changes in the punitive policy in respect of the collaborators.
Keywords: Soviet regime; partisans; collaborators; repressions